2013
DOI: 10.1245/s10434-013-3406-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis Comparing Surgically-Related Complications between Robotic-Assisted Thyroidectomy and Conventional Open Thyroidectomy

Abstract: Relative to OT, RT was associated with significantly longer operating time, longer hospital stay, and higher temporary RLN injury rate but comparable permanent complications and overall morbidity. Given some of the limitations with the literature and the potential added surgical risks and morbidity in RT, application of the robot in thyroid surgery should be carefully and thoroughly discussed before one decides on the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 39 publications
(112 reference statements)
2
75
1
3
Order By: Relevance
“…In their recent meta-analysis of 2375 patients from 11 studies, Lang et al reported longer operative times (mean difference = 56 minutes), hospital stay, and increased transient RLN injury rates in patients undergoing robotic thyroidectomy compared with those who underwent conventional transcervical thyroidectomy (21). There was no difference between the two procedures regarding blood loss, hypocalcemia, and overall morbidity.…”
Section: Comparison With Conventional Thyroidectomymentioning
confidence: 99%
“…In their recent meta-analysis of 2375 patients from 11 studies, Lang et al reported longer operative times (mean difference = 56 minutes), hospital stay, and increased transient RLN injury rates in patients undergoing robotic thyroidectomy compared with those who underwent conventional transcervical thyroidectomy (21). There was no difference between the two procedures regarding blood loss, hypocalcemia, and overall morbidity.…”
Section: Comparison With Conventional Thyroidectomymentioning
confidence: 99%
“…The blood loss is also similar. Only one meta-analysis reported a significantly higher rate of transient recurrent laryngeal nerve palsy after RT [7]. There is no significant difference in the long-term voice outcomes, assessed by VHI and GRBAS scale [11,12].…”
Section: Discussionmentioning
confidence: 95%
“…Multiple meta-analysis with large series compared RT to OT [3][4][5][6][7][8][9][10], without noticing any significant difference in most of the surgical complications: transient or permanent hypoparathyroidism, permanent recurrent laryngeal nerve palsy, hematoma, seroma... The blood loss is also similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…에서 동일하며, (183)(184)(185)189,191,(193)(194)(195)197) 수술의 합병증은 일시적 부갑상선 기능저하, (183)(184)(185)(186)(188)(189)(190)192,193,195,199) 영구적 부갑상선 지능저하, (183)(184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)199) 되돌이 후두 신경 손 상, (183)(184)(185)(186)(187)(189)(190)(191)(192)(193)(194)(195)199) 장액종, (183)(184)(185)…”
unclassified